Synthesis and Characterization of 2-Alkyl-1-[4-(5-carboxy- 1,2,3-thiadiazole-4-yl)benzyl]-4-chloro-1Himidazole- 5-carboxaldehydes - AMINI, MOHSEN; FOROUMADI, ALIREZA; VOSOOGHI, MOHSEN; VAHDATIZADEH, HAMID REZA; SHAFIEE, ABBAS (Asian Journal of Chemistry, 2010)
Starting from ethyl 4-(4-methylphenyl)-1,2,3-thiadiazole-5-carboxylate (8), 2-alkyl-1-[4-(5-carboxy-1,2,3-thidiazole-4-yl)benzyl]-4-chloro-1H-imidazole-5-carboxaldeydes (4a,4b) were prepared.